Historical Discourses about the Peruvian Independence in school textbooks: Gustavo Pons Muzzo, Pablo Macera and Editorial Santillana - Romero Meza, Eddy Walter (2022)
This article will seek to approach the historical discourses about the Peruvian Independence as presented in three school textbooks: History of Peru. Time of emancipation (1957) by Gustavo Pons Muzzo, History of Peru. Independence and Republic (1986) by Pablo Macera, and Social Sciences 3 (2020) by Editorial Santillana. To do so, the characteristics of the different authors will be analyzed (context, historiographic training, place of enunciation, etc.), their historical interpretations and the various representations they propose in school manuals. The analysis will also include some didactic elements present in school textbooks and their supplementary illustrations, in order to have an overview of the history manuals designed by the aforementioned authors. The production of school textbooks is divided within the currents of the national Creole history (Pons Muzzo), the critical national history (Pablo Macera) and the current academic history (Editorial Santillana). The work also highlights the importance of examining school textbooks beyond the image of neutral or de-ideologized pedagogical objects.